2002
DOI: 10.1002/cncr.10591
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Akt/PKB is required for suppression of cancer cell apoptosis and tumor progression in human colorectal carcinoma

Abstract: BACKGROUND Akt/protein kinase B (PKB), which is included in phosphatidyl inositol‐3‐OH kinase (PI3K) signaling, controls many intracellular processes, such as the suppression of apoptosis and the promotion of the cell cycle. Therefore, the authors investigated phosphorylated Akt (Ser473) in colorectal carcinomas to reveal the role of PI3K signaling during the development of colorectal carcinoma. METHODS Expression of phosphorylated Akt (Ser473) in two colon carcinoma cell lines (DLD‐1 and Colo205) and 65 human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
158
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(173 citation statements)
references
References 28 publications
(41 reference statements)
8
158
1
2
Order By: Relevance
“…The typical pattern of pAKT staining we observed included both cytoplasmic and nuclear immunostaining. This is consistent with most other reports for malignant cells in which the reported subcellular localisation of pAKT staining is cytoplasmic (Gupta et al, 2002;Perez-Tenorio and Stal, 2002) and nuclear (Dhawan et al, 2002;Itoh et al, 2002). Membrane staining is commonly observed in nontransformed cells and has also been reported in malignant cells though usually as a component of cytoplasmic staining (Yuan et al, 2000).…”
Section: Incidence Of Activated Akt In Pancreatic Adenocarcinoma Tumourssupporting
confidence: 91%
See 3 more Smart Citations
“…The typical pattern of pAKT staining we observed included both cytoplasmic and nuclear immunostaining. This is consistent with most other reports for malignant cells in which the reported subcellular localisation of pAKT staining is cytoplasmic (Gupta et al, 2002;Perez-Tenorio and Stal, 2002) and nuclear (Dhawan et al, 2002;Itoh et al, 2002). Membrane staining is commonly observed in nontransformed cells and has also been reported in malignant cells though usually as a component of cytoplasmic staining (Yuan et al, 2000).…”
Section: Incidence Of Activated Akt In Pancreatic Adenocarcinoma Tumourssupporting
confidence: 91%
“…In vitro data have coupled AKT to the survival pathway of the transcription factor NF-kB. This is particularly interesting given three observations: (1) the frequent constitutive activation of NF-kB in various cancers including pancreatic tumour specimens (Wang et al, 1999), (2) the nuclear immunostaining pattern of pAKT frequently observed in various tumours (Dhawan et al, 2002;Itoh et al, 2002;Perez-Tenorio and Stal, 2002), and (3) the correlation of pAKT immunostaining and nuclear localisation of the p65 subunit of NF-kB in melanoma specimens (Dhawan et al, 2002). We have previously shown in the MIA-PaCa-2 cells that AKT is coupled to NF-kB activation and alters levels of various members of the apoptosis-regulating BCL-2 family (Fahy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated MAPK was also reported in glial tumours and in a group of oligodendrogliomas, an increase in the proportions of cells expressing activated MAPK corresponded with malignant progression (Mandell et al, 1998). Sivaraman et al (Itoh et al, 2002) provided the first demonstration of MAPK activation in human breast cancer tissues, comparing primary breast cancer with benign lesions using substrate-based MAPK enzyme assays and immunoblotting. They found significantly less MAPK activity to be in benign breast tissues compared with invasive breast cancers.…”
Section: Discussionmentioning
confidence: 99%